Ethnoracial Diversity and Segregation in U.S. Rural School Districts. (31st July 2021) - Kebede, Maraki; Maselli, Annie; Taylor, Kendra; Frankenberg, Erica
Abstract: The ethnoracial diversification of rural America is gaining more attention in scholarly and policy circles, but its impact on rural school districts is often overlooked. We use federal data sources to explore the magnitude and structure of rural ethnoracial diversity and to analyze variation in how U.S. rural school district demographics have changed nationally from 2000 to 2019. Employing a majority rule typology, we classify more than 5, 000 school districts according to their ethnoracial structure. Our findings illustrate that rising Hispanic enrollment is a central element of changing rural public school student demographics nationwide. Since 2000, rural school districts have become more ethnoracially diverse, and rural students of most ethnicities/races have become less ethnoracially isolated. However, despite demographic changes resulting in more diversified district enrollments overall, segregation within rural districts persists. Furthermore, White enrollment in rural district types with the fewest White students declined twice as much as in the rural district types with the highest share of White students. Together, these patterns suggest how school segregation and opportunity hoarding can persist despite growth in districts' ethnoracial diversity.